PENGARUH GAYA HIDUP BRAND MINDED TERHADAP PERILAKU KONSUMTIF PADA MAHASISWA - Sadewa, Muhammad Ajie; Ariani, Lita (Universitas Palangka Raya, 2022)
This study aimed to determine the effect brand minded lifestyle on consumptive behavior in students. The hypothesis proposed in this study is that there is an effect of brand minded lifestyle on consumptive behavior in students. The subjects in this study were students of the Muhammadiyah University of Banjarmasin with an age range of 18-25 years, using and buying branded goods. The scale used to collect research data is a brand-minded lifestyle scale and a consumptive behavior scale. The data analysis method used in this study is a simple linear regression test. The results of this study indicate that there is a significant effect (Sig. 0.000 <0.05). These results indicate that there is an influence of the Minded brand lifestyle on the consumptive behavior of college students